2008
DOI: 10.1093/pasj/60.4.l23
|View full text |Cite
|
Sign up to set email alerts
|

Late Superhumps in WZ Sge-Type Dwarf Novae

Abstract: We report on the detection of very stable modulations with periods unexpectedly ($\sim\;$0.5%) longer than the superhump periods during the slowly fading stage of WZ Sge-type superoutbursts in three systems: GW Lib, V455 And, and WZ Sge. The periods are naturally explained by assuming that these modulations are superhumps arising from matter near the tidal truncation radius. This finding provides additional support for the hypothetical idea concerning expansion of the accretion disk well beyond the 3:1 orbital… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 36 publications
10
56
0
Order By: Relevance
“…This is in general agreement with the previous observations of other WZ Sge-type objects (see Patterson et al 1998;Kato et al 2008;Kato 2015, and references therein), although in SSS J122222 these late superhumps were seen for significantly longer time than in any other WZ Sge-type system. Moreover, the stable modulations still persisted even about 420 d after the superoutburst, but their period has further increased by about 2 per cent.…”
Section: Late Superhumpssupporting
confidence: 93%
See 1 more Smart Citation
“…This is in general agreement with the previous observations of other WZ Sge-type objects (see Patterson et al 1998;Kato et al 2008;Kato 2015, and references therein), although in SSS J122222 these late superhumps were seen for significantly longer time than in any other WZ Sge-type system. Moreover, the stable modulations still persisted even about 420 d after the superoutburst, but their period has further increased by about 2 per cent.…”
Section: Late Superhumpssupporting
confidence: 93%
“…Thus, our observations showed that long after the superoutburst SSS J122222 was still exhibiting very stable superhumps, with a period longer than that of the stage B superhumps. Post-superoutburst superhumps, also called 'late superhumps' (Vogt 1983), were observed in several other WZ Sge-type objects (see Kato, Maehara & Monard 2008;Kato 2015, and references therein). In SSS J122222, however, they were detectable for significantly longer time than in any other system.…”
Section: Post-superoutburst Modulationsmentioning
confidence: 99%
“…WZ Sge: Patterson et al 2002EG Cnc: Patterson et al 1998, GW Lib and V455 And: Kato et al 2008). Probably the best established case is GW Lib in 2007 and figure 33 in Kato et al 2009a), which showed persistent superhumps for at least 930 cycles (50 d) after the termination of the superoutburst.…”
Section: Late-stage Superhumpsmentioning
confidence: 95%
“…Although Kato et al (2008) interpreted that this increase of the period reflects the expansion of the disk after the outburst, this interpretation was probably incorrect since the pressure effect was not properly treated when comparing superhump periods. As introduced in subsection 6.2, the pressure effect shortens the superhumps period and this effect is strongest in the initial part of stage B .…”
Section: Late-stage Superhumpsmentioning
confidence: 99%
“…The stable pulsation signals reported by van Zyl et al (2000) were immediately swamped by the light from the accretion disc and an orbital superhump near 80 min became the dominant variability in the optical light curve (Kato, Maehara & Monard 2008;Bullock et al 2011). To date, several prominent signals have recurrently shown up (Copperwheat et al 2009;Schwieterman et al 2010;Bullock et al 2011;Vican et al 2011;Szkody et al 2012).…”
Section: Introductionmentioning
confidence: 93%